Shariah-Compliant Financing for Higher Education: Assessing the Potential of Hybrid Sukuk in Public Universities of Pakistan - Muhammad Arsalan Akbar; Dr. Muhammad Kaleem; Dr. Hafiz Ullah; Dr. Qaisar Bilal (Journal of Religion and Society, 2026)
This study investigates the potential of hybrid Sukuk model particularly Musharakah and Ijarah as innovative, Shariah-compliant solution for addressing infrastructure financing gaps in public sector universities of Khyber Pakhtunkhwa, Pakistan. Conventional funding channels, such as government grants and bank loans, have proven inadequate in meeting the growing infrastructural demands of higher education institutions. Against this backdrop, hybrid Sukuk present a viable alternative that combines financial innovation with ethical and religious legitimacy. The objectives of the study are twofold: first, to examine the prospects of hybrid Sukuk in bridging infrastructure funding gaps in public universities; and second, to analyze the challenges that hinder their adoption and implementation. To achieve these objectives, the study employs a qualitative methodology based on semi-structured interviews. Using purposive sampling, fifteen participants were selected, including Islamic banking experts, university professors specializing in Islamic finance, and administrators such as deputy auditors and assistant treasurers. These participants provided in-depth insights into the opportunities and risks of Sukuk adoption. Special attention was given to the hybrid Sukuk, reflecting its potential for financing projects like hostels, academic blocks, and research facilities. The findings reveal cautious receptiveness among universities, with recognition of Sukuk’s Shariah compliance and community legitimacy. However, challenges include limited institutional expertise, weak legal frameworks, misconceptions regarding Islamic finance practices, and concerns over repayment obligations. Government support, credible Shariah governance, pilot projects, and stakeholder training emerge as critical enablers of successful implementation. The study concludes that while challenges remain significant, hybrid Sukuk models represent a transformative opportunity for universities to diversify their funding sources. If supported by regulatory frameworks, institutional capacity-building, and community engagement, Sukuk financing can strengthen the financial sustainability of public universities while promoting ethical and socially responsible development. Keywords: Sukuk, Hybrid Sukuk, Musharakah, Ijarah, Public sector universities, KP, Islamic Banks